PROTECTIVE EFFECT OF ONION EXTRACT AGAINST EXPERIMENTAL IMMUNESUPPRESSION IN WISTAR RATS: BIOLOGICAL AND MOLECULAR STUDY - Alkhedaide, Adel; Soliman, Mohamed Mohamed; Ismail, Tamer Ahmed (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The wrong use of drugs results in disturbances in the immunity that affect human health. These drugshave side effects that may lead to death because of lake of immunity. Human beings need to use natural products tostrength the immune system and avoid such side effects. Of these products is the onion that used to strength theimmune system. This study was conducted to study the protective effect of onion extract on immune-suppressed ratsand its impact on the expression level of cytokines, acute phase proteins and antioxidants compared to both control andimmune suppressed groups.Materials and Methods: Forty rats were divided into four groups (10 per group) control group (CNT), immunesuppressedgroup (DEXA) injected with dexamethasone at a dose of 5 mg per kg intraperitoneally (IP) twice daily for 3days, onion extract administered group (OE) given orally at a dose of 500 mg per kg for 4 weeks. Group 4 (y), wasgiven onion extract for a week then immune-suppressed with DEXA for 3 days then continued with OE for 3 weeks.Serum and RNA were extracted for examining the biochemical and genetic changes.Results: Injection of dexamethasone decreased number of leukocytes with increase in the number of neutrophils andthe decrease of all other types of white blood cells. Moreover, a decrease in antioxidant levels such as catalase, superoxide dismutase (SOD), and reduced glutathione (GSH) with an increase in the level malondialdehyde (MDA). Inparallel, a decrease in serum levels of cytokines, such as TNF and IL-6, together with immunoglobulins (IgG and IgM),were reported in DEXA injected rats that were ameliorated by prior administration of OE. Gene expression analysisrevealed that dexamethasone suppressed gene expression of antioxidants together with IL-1 and 8 while increased IL-10 mRNA expression. All of these changes have been normalized to the normal level by OE administration to DEXAinjected rats.Conclusion: The present findings clearly emphasize the medical importance of onions as immune-stimulants at geneticand cellular levels, and that they are good for human health.